Overspecification of color, pattern, and size: salience, absoluteness, and consistency - Tarenskeen, Sammie; Broersma, Mirjam; Geurts, Bart (Frontiers in Psychology, 2015)
The rates of overspecification of color, pattern, and size are compared, to investigate how salience and absoluteness contribute to the production of overspecification. Color and pattern are absolute and salient attributes, whereas size is relative and less salient. Additionally, a tendency toward consistent responses is assessed. Using a within-participants design, we find similar rates of color and pattern overspecification, which are both higher than the rate of size overspecification. Using a between-participants design, however, we find similar rates of pattern and size overspecification, which are both lower than the rate of color overspecification. This indicates that although many speakers are more likely to include color than pattern (probably because color is more salient), they may also treat pattern like color due to a tendency toward consistency. We find no increase in size overspecification when the salience of size is increased, suggesting that speakers are more likely to include absolute than relative attributes. However, we do find an increase in size overspecification when mentioning the attributes is triggered, which again shows that speakers tend to refer in a consistent manner, and that there are circumstances in which even size overspecification is frequently produced.